Implementation of Child Protection Policy for Victims of Domestic Violence in Kabupaten Tegal - Nala Teliana Teliana; Johanna Debora Imelda (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP),UIN Syarif Hidayatullah Jakarta, 2026)
This study aims to explain the implementation of child protection policies for child victims of domestic violence based on three of the six variables of policy implementation theory proposed by Van Meter and Van Horn (1975), within the context of child protection policies in Tegal Regency. Existing child protection policies, from the national to the regional level, have not yet succeeded in reducing the overall incidence of violence against children nationwide. Data from the SIMFONI PPA in 2024 indicate that cases of violence against children continue to increase. This study employs a descriptive qualitative method, with data collected through interviews, observations, and document analysis. In addition, the researcher examined government policy documents as well as relevant previous studies. The findings reveal that among the six variables—policy objectives, resources, and inter-organizational relationships—only certain variables have been optimally implemented to support the effective implementation of child protection policies in Tegal Regency. Significant improvements are still required to optimize the implementation of child protection policies.